Comparison of Min-Max and EOQ Methods in Web-Based Stock Management Information System - Dharmakirti, Dharmakirti; Ngemba, Hajra Rasmita; Hendra, Syaiful; Syahrullah, Syahrullah; Nugraha, Deny Wiria; Dwiwijaya, Kadek Agus (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Warehouse stock management is very important for the sustainability of a business, especially building stores that have a lot of goods. Many problems occur in the absence of stock information management in a business. This happens at Pelita Building Store which has a lot of goods so it is very difficult for the owner to decide which items to stock based on priority. This study aims to help business owners to carry out stock management by comparing two inventory methods, namely the Economic Order Quantity (EOQ) and Min-Max methods. The comparison is carried out with the aim of determining the most optimal method that can be used for stock management in the building shop business case. This research uses a system development method by adopting the prototype method. This research was tested by conducting blackbox and accuracy testing. The results of this study based on blackbox testing stated that the features in the application function properly and can be used for stock management. In addition to black box testing, accuracy testing is also carried out. Accuracy testing is done by comparing the data from the information system calculation with the data from the manual calculation. After comparison, an accuracy of 100% is obtained, thus it can be concluded that this application can be used to help shop owners determine priority stock and the most accurate method is to use the EOQ method